2008
DOI: 10.1264/jsme2.23.89
|View full text |Cite
|
Sign up to set email alerts
|

Expressed nifH Genes of Endophytic Bacteria Detected in Field-Grown Sweet Potatoes (Ipomoea batatas L.)

Abstract: We examined the nitrogenase reductase (nifH) genes of endophytic diazotrophic bacteria expressed in field-grown sweet potatoes (Ipomoea batatas L.) by reverse transcription (RT)-PCR. Gene fragments corresponding to nifH were amplified from mRNA obtained from the stems and storage roots of field-grown sweet potatoes several months after planting. Sequence analysis revealed that these clones were homologous to the nifH sequences of Bradyrhizobium, Pelomonas, and Bacillus sp. in the DNA database. Investigation of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
54
0
3

Year Published

2009
2009
2021
2021

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 72 publications
(58 citation statements)
references
References 45 publications
1
54
0
3
Order By: Relevance
“…This indicated that this gene was induced under the treatment without a nitrogen source. Similarly, TerakadoTonooka et al (34) suggested that bradyrhizobia colonize and express the nifH gene not only in the root nodules of leguminous plants but also in sweet potatoes as diazotrophic endophytes. However, it has been observed that R. leguminosarum bv.…”
Section: Discussionmentioning
confidence: 99%
“…This indicated that this gene was induced under the treatment without a nitrogen source. Similarly, TerakadoTonooka et al (34) suggested that bradyrhizobia colonize and express the nifH gene not only in the root nodules of leguminous plants but also in sweet potatoes as diazotrophic endophytes. However, it has been observed that R. leguminosarum bv.…”
Section: Discussionmentioning
confidence: 99%
“…Although there have been many attempts to describe the diversity of nifH gene pools in environmental samples (6,7,9,12,19,30,31,33), few studies have simultaneously displayed both qualitative and quantitative differences in nifH gene composition (18,26,27,32). Phylogenetic trees have been frequently used to describe visually the microbial diversity in diverse environments.…”
Section: Diversity Of the Nifh Gene In The Rhizosphere Of M Malabathmentioning
confidence: 99%
“…After 15-years long molecular investigations, we successfully identified the possible candidates of endophytic free-living N 2 -fixing rhizobia habiting in the plant tissues such as sugarcane stems 91) and sweet potato petioles. 92) Wild plants, whose roots form the symbiotic system with arbuscular mycorrhiza, show a preference for the uptake of ammonia and amino acids, which are released from decomposing plant residues and whose δ 15 N values are higher than that of the nitrate produced from them by nitrification. Therefore, arbuscular mycorrhiza-infected plants have δ 15 N values, higher than those of non-infected plants, 93) but other types of fungi, i.e., ectomycorrhizal and saprotrophic fungi, do not follow this rule.…”
Section: Introductionmentioning
confidence: 99%